Characteristics of the carotid intima-media thickness and atherosclerotic plaques of carotid arteries in elderly people with rheumatoid arthritis at University Medical Center Ho Chi Minh City - Cao, Thanh Ngoc; Dang, Ngoc Son (Tạp chí Y Dược Huế, 2023)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease that has been strongly associated with atherosclerosis. Comprehensive cardiovascular disease (CVD) assessment is advised, which entails screening for asymptomatic atherosclerotic plaques using carotid ultrasound. The objective of this study is to examine the features of carotid ultrasound, including carotid intima-media thickness (cIMT) and carotid plaques (CP), and to compare these characteristics between individuals with RA and control subjects. Materials and Methods : A cross-sectional study involved 66 participants, including 40 RA patients and 26 controls. Medical history and physical examination were conducted by a rheumatologist, while cIMT and CP were recorded via carotid ultrasound. Results: cIMT was significantly higher in the RA group compared to the control group (0.94 (0.83 - 1.25) mm vs 0.84 (0.80 - 0.92) mm, p = 0.030) and the prevalence of increased cIMT was found significantly higher in RA-patients than non-RA patients (70.00% vs 38.46%, p = 0.011). Compared to non-RA patients, carotid plaques in the RA group were statistically more prevalent on either side of the carotid artery (left 57.50% vs. 26.92%, p = 0.015; right 67.50% vs 26.92%, p = 0.001) and bilateral CP was over three times more common in RA than controls (55.00% vs 15.38%, p = 0.001). cIMT was correlated with age and body mass index. Conclusion: The occurrence of subclinical atherosclerosis is higher among patients with RA than in the control participants without RA. Measuring cIMT and CP may be a useful guide to better assess CVD risk in patients with RA and enable clinicians to take interventions promptly.